Immobilization of lipase from Thermomyces lanuginosus and its Glycerolysis ability in diacylglycerol preparation - Xie, Rui; Lee, Yee Ying; Xie, Pengkai; Tan, Chin Ping (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
In the glycerolysis process for diacylglycerol (DAG) preparation, free lipases suffer from poor stability and the inability to be reused. To address this, a cost-effective immobilized lipase preparation was developed by cross-linking macroporous resin with poly (ethylene glycol) diglycidyl ether (PEGDGE) followed by lipase adsorption. The selected immobilization conditions were identified as pH 7.0, 35 °C, cross-linking agent concentration 2.0%, cross-linking time 4 h, lipase amount 5 mg/g of support, and adsorption time 4 h. Enzymatic properties of the immobilized lipase were analyzed, revealing enhanced pH stability, thermal stability, storage stability, and operational stability post-immobilization. The conditions for immobilized enzyme-catalyzed glycerolysis to produce DAG were selected, demonstrating the broad applicability of the immobilized lipase. The immobilized lipase catalyzed glycerolysis reactions using various oils as substrates, with DAG content in the products ranging between 35 and 45%, demonstrating broad applicability. Additionally, the changes during the repeated use of the immobilized lipase were characterized, showing that mechanical damage, lipase leakage, and alterations in the secondary structure of the lipase protein contributed to the decline in catalytic activity over time. These findings provide valuable insights for the industrial application of lipase.